Assessment of the variation and influencing factors of vegetation NPP and carbon sink capacity under different natural conditions. (May 2022) - Wei, Xindong; Yang, Jie; Luo, Pingping; Lin, Liangguo; Lin, Kangli; Guan, Jiamin
Highlights: NPP and carbon sink capacity showed an increasing trend. NPP is more sensitive to precipitation than temperature in Shaanxi. NPP shows a bimodal variation with elevation in Shaanxi. NPP changes caused by land use are related to the structural differences and the transfer between different land use types. Abstract: Exploring the spatiotemporal variation in vegetation net primary productivity (NPP), analyzing the relationships between NPP and its influencing factors, and evaluating the vegetation carbon sink capacity are vital for ecological protection and restoration in Shaanxi Province, an area in China with a complex environment. In this study, the Mann-Kendall trend test, difference analysis, and variation stability analysis were used to analyze the spatiotemporal variation in NPP; partial correlation analysis and a land use change matrix were used to analyze the relationships between NPP and its influencing factors; and an estimation model of net ecosystem productivity (NEP) was used to evaluate the carbon sink capacity of vegetation based on the NPP product of the MOD17A3HGF dataset. The following results were obtained. (1) The average annual NPP in Shaanxi showed an increasing trend from 2000 to 2019, and its variation stability showed an increasing trend from the north to the south. (2) The average annual NPP in the south was higher than that in the north, but the increased amplitude of NPP was higher in the north and lower in the south. (3) The vegetation carbon sink capacity in Shaanxi showed an increasing trend from 2000 to 2019, and it was high in the south and low in the north. (4) NPP was more sensitive to precipitation than temperature in Shaanxi, and NPP showed a bimodal variation with elevation. The NPP changes caused by land use were related to the structural differences and the transfer between different land use types. This study provides a new perspective for the simultaneous study of spatiotemporal variation in NPP and carbon sink capacity under different natural conditions and the exploration of the factors influencing this variation. These findings are valuable for the scientific assessment of regional vegetation productivity and carbon sink capacity, as well as for the formulation of development strategies based on local realities. Our results indicate that the ecological environment in Shaanxi continuously improved in recent years, and further improvements to water resource conditions and ecological construction efforts are essential for improving the NPP and carbon sink capacity in Shaanxi.